Pengaruh Kafein Terhadap Lengkung Ekor Spermatozoa Epididimis Sapi Bali - Oktora Dwi Putranti (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2018)
This study aims to analyze the influence of caffeine on the distance of the tail movement of the spermatozoa epididymis cattle Bali. Methods in this study with a collection of sperm from Slaughter House (RPH) and then conducted the process of freezing with Tris yolk dilution. Treatment of caffeine with levels of 0 mg/ml, 2 mg/ml, 4 mg/ml and 6 mg/ml in spermatozoa that have been in thawing. The variables observed were DCL, DAP, DSL, ALH analyzed by CASA. Results showed no difference (P> 0.05) motility with caffeine treatment and short sperm tailwave distance of 37.27 μm showed the sperm motility velocity. Keywords: spermatozoa tail, caffeine